PROFIL PEMERIKSAAN INDEKS PROLIFERATIF KI-67 PADA PENDERITA KANKER PAYUDARA DI RSUD ARIFIN ACHMAD TAHUN 2010-201 - Syukri, Nodia Adillah; Fidiawati, Wiwit Ade; Tripriadi, Effif Syofra (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTBreast cancer is a malignancy in breast tissue when cells grow abnormallyuncontrolled and invade to other parts of the body. Some biomarkers that already recognizedin breast cancer are Estrogen Receptor (ER), Progesterone Receptor (PR), HumanEpidermal Growth Factor Receptor-2 (HER-2), Ki-67 Proliferation Index and Cytokeratin(CK5). Ki-67 Proliferation index examination can be used to predict recurrence and clinicaloutcome of breast malignancy, Ki-67 also may helpful to determine response ofchemotherapy. This study aims to present the profile of Ki-67 examination on breast cancerpatients at Arifin Achmad General Hospital in 2010-2015. This study using retrospectivecross-sectional and descriptive observational method. The population of this study are allpatients diagnosed with breast cancer based on histopathology examination with Ki-67proliferation index at Arifin Achmad General Hospital’s histopathology laboratory in 2010-2015. Six years breast cancer data were analysed, the result of the study are almost allhistological type of breast cancer is Invasive Ductal Carcinoma (IDC) with 350 cases(92,8%) and most of them are <50 years old, the most frequent histological grade is grade IIwith 203 cases (53,8%) and Luminal B as the most frequent molecular type of breast cancerwith 159 cases (42,1%), most of them are categorized as high expression of Ki-67 index with325 cases (86,2%).Keywords: breast cancer, Ki-67 proliferation index, invasive ductal carcinoma,Ki-67 high expression.